Evolution of gene knockout strains of E. coli reveal regulatory architectures governed by metabolism - Douglas McCloskey (Nature Portfolio, 2018)
The function of metabolic genes in the context of regulatory networks is not well understood. Here, the authors investigate the adaptive responses of E. coli after knockout of metabolic genes and highlight the influence of metabolite levels in the evolution of regulatory function.